Regional discontinuities and the effectiveness of further training subsidies for low-skilled employees - Christine Martina Dauth (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2017)
I analyze the effects of further training subsidies for low-skilled employees on individual labor market outcomes in Germany for the period from 2007 to 2012. Using detailed administrative data, I exploit cross-regional variation in the conditional policy styles of local employment agencies and use this fuzzy discontinuity as an instrument for program participation. I find that subsidies significantly increase cumulative employment duration and earnings for the subgroup of compliers. These gains are particularly pronounced for workers who are women, younger than 35 years old, non-German citizens and participated before the economic crisis of 2009. – – In diesem Beitrag untersuche ich die Wirkung von Weiterbildungssubventionen auf die Arbeitsmarktchancen von gering Qualifizierten zwischen 2007 und 2012. Mit Hilfe detaillierter Prozessdaten bestimme ich Unterschiede in den konditionalen Politikstilen zwischen den lokalen Arbeitsagenturen und nutze diese unscharfe Diskontinuität als Instrument um kausale Effekte zu identifizieren. Für "complier", d.h. Personen, die die Subventionen nur aufgrund eines bestimmten Politikstils einer Arbeitsagentur erhalten, erhöhen sich aggregierte Beschäftigung und Einkommen. Besonders stark profitieren dabei Frauen, unter 35jährige, Personen ohne deutsche Staatsbürgerschaft und Teilnehmer in den Jahren vor der Wirtschaftskrise von 2009.
Keywords: J18; J24; J31; I21; 330; further training for employees; low-skilled workers; instrumental variables; regional discontinuity